Implementasi Iklan Layanan Masyarakat Menggunakan Teknik Motion Graphics pada Alur Pembuatan Kartu Tanda Penduduk Elektronik - Meiyi Darlies; Tauriq, Alparizqi; Yulian Mirza (Jurnal Teknologi Informatika Multimedia Digital, 2024)
Each sub-district and the Indonesian Population and Civil Registration Office has a path to make Electronic Identity Cards to the public. The presentation of information on making Electronic Identity Cards still has shortcomings, which are mostly in the form of text. One drawback of this is the lack of providing interesting information absorption activities and is poorly understood so that it stimulates curiosity when compared textually. Therefore, a delivery medium is needed, namely by making a motion graphics that can support the development of information on making Electronic Identity Cards in Districts and Civil Registration that is useful for the community as reference material in the process of making new Electronic Identity Cards, moves/arrivals, data changes, damaged or lost for Indonesian citizens. The research and development methods used in this study are the Multimedia Development Life Cycle method and Cohen’s Kappa consistency test. This study produced a video of 6 minutes 51 seconds in .mp4 format. This animated video gets a percentage index of the test results with Cohen’s Kappa which gets the result: "medium" at "0.545455" with a medium category in terms of video quality or video content in the form of knowledge and the importance of making an E-KTP for Indonesian citizens